Imaginary capital migration and the competitive politics of corporate taxation - Jaakkola Jussi; Ylönen Matti; Saari Leevi (Routledge, Taylor & Francis, 2022)
International competitiveness has solidified itself as a key policy goal for nation states. The consequent competitive re-design of tax systems has reduced corporate tax rates across borders. To understand the policy-shaping nature of tax competition, we examine how the changing imagery of competitiveness has rationalised lowering the corporate tax rate in three Finnish tax reforms since the 1990s. In attracting mobile capital by inventing tax system disparities, governments increasingly rely on imaginary capital migration. Examining imaginary capital migration demonstrates that governments’ competitive policies of fiscal nationalism greatly overlap with corporate taxpayers’ tax avoidance arrangements, as both practices are largely disembedded from the material dynamics of economy.